2008
DOI: 10.1254/jphs.fp0072106
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression Induced by a Conditioned Stimulus Associated With Cocaine Self-Administration

Abstract: Abstract. Cocaine addiction is known to impair immune system function, but the effects of repeated treatment with cocaine in a self-administration model, its withdrawal as well as reinstatement of cocaine-seeking behavior on cell-mediated immunity are not well known. Cocaine self-administered for 18 days induced a significant increase in spleen weight, plasma corticosterone levels, interleukin (IL)-10, and tumor necrosis factor-α production, while concanavalin A-stimulated proliferation responses of peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
(21 reference statements)
4
20
2
1
Order By: Relevance
“…This explanation is supported by evidence of an upward shift in dose response for METH selfadministration and higher motivation for METH in TNF-α (−/−) mice. Our results are also consistent with recent reports suggesting an association between TNF-α and cocaine or heroin self-administration (Kubera et al 2008;Weber et al 2009). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This explanation is supported by evidence of an upward shift in dose response for METH selfadministration and higher motivation for METH in TNF-α (−/−) mice. Our results are also consistent with recent reports suggesting an association between TNF-α and cocaine or heroin self-administration (Kubera et al 2008;Weber et al 2009). …”
Section: Discussionsupporting
confidence: 93%
“…Some reports show that the level increases (Gonzalez-Quintela et al 2008;Peng et al 1999;Irwin et al 2009), and others show that the level decreases or does not change (Baldwin et al 1997;Irwin et al 2007;Sacerdote et al 2008;Li et al 2009;Franchi et al 2010). In animals, repeated administration of psychostimulants or opiates induced TNF-α production in the brain or immune system (Friedman and Eisenstein 2004;Nakajima et al 2004;Niwa et al 2007a; Kubera et al 2008). TNF-α knockout (TNF-α (−/−)) mice are more sensitive to methamphetamine (METH)-or morphineconditioned place preference than wild-type animals (Nakajima et al 2004;Niwa et al 2007a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Mao and associates reported that cocaine downregulates IL-2-induced production of lymphocytes [50]. Cocaine has also been shown to increase levels of IL-10, which is an anti-inflammatory cytokine [5153]. These stimulatory effects on the anti-inflammatory cytokines have not been shown for amphetamines and may explain the marked difference in leukocytosis between the amphetamine and cocaine subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Given the connectivity of the hypothalamus with the autonomic nervous system and its control over the release of various peripheral neuroendocrine mediators, this brain region may serve as the relay between the CNS and the immune system. For example, cocaine-associated cues induce concomitant alterations in immune functioning, including TNF-α production, and in corticosterone levels, suggesting the HPA axis may be involved in drug cue-mediated conditioned immunomodulation (Kubera et al, 2008). Alternatively, the sympathetic nervous system innervates both primary and secondary lymphoid tissues and releases molecules that interact with receptors on immune cells (Williams et al, 1981; Felten et al, 1984).…”
Section: Discussionmentioning
confidence: 99%